Configurations of the real in Chinese literary and aesthetic modernity - Button, Peter (Ideas, history, and modern China,, 2009)
"Tracing the formation of the modern concept of literature in 20th century China, this book examines the emergence of the Chinese socialist realist novel in relation to the literary and philosophical currents globalized in the wake of capitalist modernity"--Provided by publisher.